Enhancing the alignment of the preclinical and clinical stroke recovery research pipeline: Consensus-based core recommendations from the Stroke Recovery and Rehabilitation Roundtable translational working group. Issue 5 (July 2017) - Corbett, Dale; Carmichael, S Thomas; Murphy, Timothy H; Jones, Theresa A; Schwab, Martin E; Jolkkonen, Jukka; Clarkson, Andrew N; Dancause, Numa; Weiloch, Tadeusz; Johansen-Berg, Heidi; Nilsson, Michael; McCullough, Louise D; et al.
Stroke recovery research involves distinct biological and clinical targets compared to the study of acute stroke. Guidelines are proposed for the pre-clinical modeling of stroke recovery and for the alignment of pre-clinical studies to clinical trials in stroke recovery.